2D shear-wave ultrasound elastography (SWE) evaluation of ablation zone following radiofrequency ablation of liver lesions: is it more accurate? - Bo, Xiao W (Br J Radiol, 2016)
OBJECTIVE: To evaluate the usefulness of two-dimensional quantitative ultrasound shear-wave elastography (2D-SWE) [i.e. virtual touch imaging quantification (VTIQ)] in assessing the ablation zone after radiofrequency ablation (RFA) for ex vivo swine livers. METHODS: RFA was performed in 10 pieces of fresh ex vivo swine livers with a T20 electrode needle and 20-W output power. Conventional ultrasound, conventional strain elastography (SE) and VTIQ were performed to depict the ablation zone 0 min, 10 min, 30 min and 60 min after ablation. On VTIQ, the ablation zones were evaluated qualitatively by evaluating the shear-wave velocity (SWV) map and quantitatively by measuring the SWV. The ultrasound, SE and VTIQ results were compared against gross pathological and histopathological specimens. RESULTS: VTIQ SWV maps gave more details about the ablation zone, the central necrotic zone appeared as red, lateral necrotic zone as green and transitional zone as light green, from inner to exterior, while the peripheral unablated liver appeared as blue. Conventional ultrasound and SE, however, only marginally depicted the whole ablation zone. The volumes of the whole ablation zone (central necrotic zone + lateral necrotic zone + transitional zone) and necrotic zone (central necrotic zone + lateral necrotic zone) measured by VTIQ showed excellent correlation (r = 0.915, p < 0.001, and 0.856, p = 0.002, respectively) with those by gross pathological specimen, whereas both conventional ultrasound and SE underestimated the volume of the whole ablation zone. The SWV values of the central necrotic zone, lateral necrotic zone, transitional zone and unablated liver parenchyma were 7.54–8.03 m s(−1), 5.13–5.28 m s(−1), 3.31–3.53 m s(−1) and 2.11–2.21 m s(−1), respectively (p < 0.001 for all the comparisons). The SWV value for each ablation zone did not change significantly at different observation times within an hour after RFA (all p > 0.05). CONCLUSION: The quantitative 2D-SWE of VTIQ is useful for the depiction of the ablation zone after RFA and it facilitates discrimination of different areas in the ablation zone qualitatively and quantitatively. This elastography technique might be useful for the therapeutic response evaluation instantly after RFA. ADVANCES IN KNOWLEDGE: A new quantitative 2D-SWE (i.e. VTIQ) for evaluation treatment response after RFA is demonstrated. It facilitates discrimination of the different areas in the ablation zone qualitatively and quantitatively and may be useful for the therapeutic response evaluation instantly after RFA in the future.